Konzeption einer finanzwirtschaftlichen Bewertungssystematik für geschlossene Fonds in Verkaufsprospekten und Leistungsnachweisen - Michael Hertel; Robin Zorzi (Credit and Capital Markets – Kredit und Kapital, 2015)
Die jüngste aus der nationalen Umsetzung der Alternativen Investment Fondsmanager-Richtlinie (AIFM-Richtlinie) der Europäischen Union in Deutschland hervorgehende Kapitalmarktregulierung sieht neue Informationspflichten für geschlossene Publikumsfonds vor. Allerdings erlauben diese aufgrund fehlender Operationalisierungsvorgaben nur bedingt eine transparente, verständliche und standardisierte Aufbereitung finanzwirtschaftlicher Informationen für private Investoren. Der vorliegende Beitrag stellt unter Berücksichtigung der neuen Publizitätsvorgaben des Kapitalanlagegesetzbuches (KAGB) bzw. geplanter Vorgaben des Instituts der Wirtschaftsprüfer (IDW) sowie bestehender finanzwirtschaftlicher Methoden eine Bewertungssystematik für geschlossene Publikumsfonds vor, die zu mehr Produkttransparenz und einer besseren Vergleichbarkeit führen kann. Die Anwendung der vorgeschlagenen Bewertungssystematik wird hierbei unter Zugrundelegung realer Fondsdaten aufgezeigt. – – Development of a Valuation System for Closed-Ended Alternative Investment Funds in Sales Prospectuses and Performance Reports The recent implementation of the European Alternative Investment Funds Managers Directive (AIFMD) into German law contains new information regulations for closed-ended alternative investment funds (AIF) in order to protect private investors. However, they hardly address a comprehensive presentation of financial product information due to the existing lack of operationalizing standards. Considering the new regulation of the German Capital Investment Statute Book (Kapitalanlagegesetzbuch – KAGB) and future standards of the German Institute of Auditors (IDW), this paper suggests a new valuation system for closed-ended AIFs for private investors based on cash flows and well-established finance methods. Thereby, the objective is to accomplish a higher level of product transparency and comparability. Using a data sample of real closed-ended AIFs, standards for the design of the financial information that has to be published to capital markets by emission houses are provided.
Keywords: M48; G23; G32; 330; capital market regulation; closed-ended alternative investment funds; investor information; financial valuation system